2022
DOI: 10.1021/acs.analchem.2c00439
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an APE1-Mediated Cascade Signal Amplification Platform for Homogeneously Sensitive and Rapid Measurement of DNA Methyltransferase in Escherichia coli Cells

Abstract: DNA methylation is an essential genomic epigenetic behavior in both eukaryotes and prokaryotes. Deregulation of DNA methyltransferase (Dam MTase) can change the DNA methylation level and cause various diseases. Herein, we develop an apurinic/apyrimidinic endonuclease 1 (APE1)-mediated cascade signal amplification platform for homogeneously sensitive and rapid measurement of Dam MTase in Escherichia coli cells. This assay involves a partial double-stranded DNA (dsDNA) substrate and two hairpin signal probes (HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 51 publications
(129 reference statements)
0
3
0
Order By: Relevance
“…Besides, we further examined the real‐time fluorescence results from the proposed program processed by other DNA adenine MTase (Dam). [ 24 ] We found that the fluorescence intensity gradually increased upon adding M.SssI and reached a plateau at 100 min, while it remained very low when M.SssI was replaced with Dam (Figure 2C). Altogether, these results demonstrated that the present circuit was viable for accurate and selective M.SssI detection.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, we further examined the real‐time fluorescence results from the proposed program processed by other DNA adenine MTase (Dam). [ 24 ] We found that the fluorescence intensity gradually increased upon adding M.SssI and reached a plateau at 100 min, while it remained very low when M.SssI was replaced with Dam (Figure 2C). Altogether, these results demonstrated that the present circuit was viable for accurate and selective M.SssI detection.…”
Section: Resultsmentioning
confidence: 99%
“…3−5 Therefore, sensitively measuring Dam MTase is of high significance for methylation detection and early clinical diagnosis. 6 To date, various conventional strategies have been developed for Dam MTase detection, including high-performance liquid chromatography, radioactive labeling-based gel electrophoresis, enzyme-based immunoassay, and capillary electrophoresis. 7−10 Nevertheless, the involvement of radiolabeled substrates, timeconsuming procedures, and costly antibodies severely limits their wide applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…DNA methylation is an important epigenetic modification catalyzed by DNA methyltransferase (Dam MTase), which plays a crucial role in the regulation of gene transcription, gene silencing, genome integrity, and cell development , Aberrant DNA methylation is usually caused by abnormal expression of Dam MTase, resulting in various human diseases, including genetic diseases, autoimmune disease, and cancers. Therefore, sensitively measuring Dam MTase is of high significance for methylation detection and early clinical diagnosis . To date, various conventional strategies have been developed for Dam MTase detection, including high-performance liquid chromatography, radioactive labeling-based gel electrophoresis, enzyme-based immunoassay, and capillary electrophoresis. Nevertheless, the involvement of radiolabeled substrates, time-consuming procedures, and costly antibodies severely limits their wide applications .…”
Section: Introductionmentioning
confidence: 99%